Ageing phenomena without detailed balance: the contact process - Enss, Tilman (Journal of physics. A, Mathematical and theoretical, 2004)
The long-time dynamics of the 1D contact process suddenly brought out of an uncorrelated initial state is studied through a light-cone transfer-matrix renormalization group approach. At criticality, the system undergoes ageing which is characterized through the dynamical scaling of the two-times autocorrelation and autoresponse functions. The observed non-equality of the ageing exponents a and b excludes the possibility of a finite fluctuation-dissipation ratio in the ageing regime. The scaling form of the critical autoresponse function is in agreement with the prediction of local scale invariance.
Gesehen am 24.11.2017